IGods : how technology shapes our spiritual and social lives - Detweiler, Craig, 1964- (Grand Rapids, Michigan : Brazos Press, 2014)
Today the world is literally at our fingertips. We can call, text, email, or post our status to friends and family on the go. We can carry countless games, music, and apps in our pocket. Yet it's easy to feel overwhelmed by access to so much information and exhausted from managing our online relationships and selves. Craig Detweiler, a nationally known writer and speaker on media issues, provides needed Christian perspective on navigating today's social media culture. He interacts with major symbols, or "iGods," of our distracted age--Google, Facebook, Amazon, Apple, Pixar, YouTube, and Twitter--to investigate the impact of the technologies and cultural phenomena that drive us. Detweiler offers a historic look at where we've been and a prophetic look at where we're headed, helping us sort out the immediate from the eternal, the digital from the divine.
Introduction: iGods -- Defining technology -- Apple: aesthetics first -- A brief history of the Internet -- Amazon: personalized abundance -- Google: algorithmic authority -- A brief history of social networking -- Facebook: authentic frenemies -- YouTube, Twitter, Instagram: audience participation -- Conclusion: the telos of technology.
Includes bibliographical references (pages 227-242) and index.
Keywords: Technology -- Religious aspects -- Christianity; Social networks; Social networks; Technology -- Religious aspects -- Christianity